Switching from adalimumab to tofacitinib in the treatment of patients with rheumatoid arthritis. Issue 1 (December 2016) - Genovese, Mark; van Vollenhoven, Ronald; Wilkinson, Bethanie; Wang, Lisy; Zwillich, Samuel; Gruben, David; Biswas, Pinaki; Riese, Richard; Takiya, Liza; Jones, Thomas
Abstract Background Tofacitinib is an oral Janus kinase inhibitor for the treatment of rheumatoid arthritis (RA). The aim of this study was to explore the safety and efficacy of open-label tofacitinib following blinded treatment with adalimumab or tofacitinib for moderate to severe RA. Methods Analyses included patients treated with adalimumab 40 mg once every 2 weeks or tofacitinib 10 mg twice daily (BID) with background methotrexate (MTX) in a 12-month randomized study (NCT00853385), who subsequently received tofacitinib 10 mg BID (with/without background MTX) in an open-label extension (NCT00413699). Patients with treatment-related serious adverse events (AEs) and serious or recurrent infections in the index study were excluded from the extension study. Exposure-adjusted incidence rates of safety-related events were assessed in 3-month and 12-month periods in the year before and in the year after switching. Efficacy was assessed 3 months before, at the time of, and 3 months after switching. Results There were 233 (107 adalimumab to tofacitinib 10 mg BID, 126 blinded to open-label tofacitinib 10 mg BID) patients included in these analyses. Patients in both treatment sequences had similar incidence rates (per 100 patient-years) of discontinuation due to AEs, serious AEs, and serious infections in the year before and in the year after switching. Incidence rates of AEs were increased in the first 3 months after switching compared with the last 3 months before switching in both treatment groups. Switching from either blinded adalimumab or tofacitinib to open-label tofacitinib resulted in numerically higher incidence of responders for signs and symptoms of disease and improved physical function. Conclusions Treatment can be directly switched from adalimumab to tofacitinib. A similar safety and efficacy profile was seen when patients received open-label tofacitinib after receiving either blinded adalimumab or tofacitinib. Trial registration ClinicalTrials.gov Identifiers:NCT00853385, registered 27 February 2009;NCT00413699, registered 18 December 2006.